Selection of Judges for Administrative Courts - Deviatnikovaitė, Ieva (Teisė, 2021)
Administrative law, unlike civil or criminal law, is not a codified branch of law and it is characterized by a large number of sources of different legal force. Thus, a judge hearing administrative disputes must have particularly deep knowledge of administrative law. The article analyzes the experience of France, Germany, the Czech Republic, Slovakia, Poland, and Lithuania in selecting candidates for judges to work with administrative cases.